Analysis of the use of transosseous osteosynthesis in the treatment of patients with diabetic osteoarthropathy complicated by chronic osteomyelitis - Anatoly S. Sudnitsyn; Nikolai M. Kliushin; Tatyana A. Stupina; Galina V. Diachkova (Гений oртопедии, 2023)
Relevance Diabetic neuroosteoarthropathy (DNOAP) complicated by chronic osteomyelitis (CO) is one of the most common complications (up to 7.5 %) in patients with diabetes mellitus. Treatment failure of such patients leads to amputation of the segment, and in some cases, to death. The use of the method of transosseous osteosynthesis is the only alternative method in the struggle for the limb salvage. Purpose Based on X-ray morphological criteria for assessing bone quality, to determine the optimal assembly of the external fixation device (EFF), which provides favorable conditions for restoring limb weight-bearing capacity in the treatment of patients with DNOAP complicated by infection. Materials and methods The analysis of radiographs and the clinical course of the reparative process in 49 patients (mean age 55.5 ± 9.4 years) with DNOAP complicated by chronic osteomyelitis was carried out. Two groups were distinguished based on the Ilizarov apparatus assembly: wire-based (WB) used in 25 patients; hybrid construct (HC) in 24 patients. The X-ray obtained in Jpeg format were analyzed using specialized Hi-scene software. The density of the bones of the foot was studied by MSCT. Results Comparison of the indicators of bone optical density in both study groups showed that there was an insignificant increase in the postoperative period Od of the calcaneus by 25 % after treatment in patients from the HC group, and in the WB group by 43 % in the distal tibia. At the same time, we noted a significant increase in the Od values of the tibia in the postoperative period in patients from the HC group and in the body of the calcaneus in patients from the WB group. MSCT showed that the density of the calcaneus before treatment in patients with DNOAP in the region of the calcaneal tubercle was 194.37 ± 49.05 HU, in the region of the body it was 205.47 ± 38.36 HU, in the region of the distal tibia 280.00 ± 40.30 HU. The analysis of the results of bone osteosynthesis of the affected segment showed that the rate of satisfactory outcomes after dismantling the device in patients from the HC group was significantly higher than in the WB group (56 %) and amounted to 75 %. Discussion As is known, pronounced osteoporosis of the bones of the lower leg and foot is often characteristic of patients with diabetes mellitus complicated by DNOAP and chronic osteomyelitis. A possible arsenal of treatment methods that allow solving the problems of stable arrest of the osteomyelitic process and restoring limb support in such patients is very limited. The optimal choice of the Ilizarov apparatus assembly type has an impact on the outcome of treatment of patients with this pathology. Conclusion Based on X-ray morphological criteria for assessing bone quality, our study showed a decrease in optical and densitometric bone density in patients with DNOAP complicated by chronic osteomyelitis compared to the norm. The use of wire-based assembly of the apparatus does not provide sufficient conditions for the solution of the set of the surgical tasks in this category of patients. The introduction of half-pins into the apparatus system provides the necessary fixation time with the possibility of functional load on the operated segment in patients in the postoperative period.